POTENSI PEMANFAATAN LAHAN PEKARANGAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN PETANI SAYURAN DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Zulkarnain Zulkarnain (Jurnal WACANA PERTANIAN, 2014)
Potential For Land Use Yard And Its Contribution To Revenue Farmers Vegetables In District Gisting Tanggamus.(Nurul Cahyani). Yard is open land located around the house tinggal.Luas yards in Indonesia reached 7.7 million hectares (Rohaidah, 2014) .Lahan yard has potential in the Provision of food can increase the family and household income of farmers, but a number of constraints often encountered in the yard of land use, which are still to be odd and not market-oriented, Hence the necessary planning and utilization of support in their yards so that they can more optimal.Penelitian aims to: (1) determine the total income of vegetable farmers in farmland non yard and yards in the village of Upper Subdistrict  Gisting Tanggamus; (2) determine the contribution income of farmers of vegetables in home gardens in the village of  Upper Subdistrict Gisting Gisting Tanggamus. The method used to calculate the income of farmers is the analysis of income. As for calculating the contribution of farmers using the formula contribution analysis. The research was conducted in the village of Upper Subdistrict Gisting Gisting Tanggamus. These results indicate that (1) Average earned income of farmers in non yard land is Rp. 11,108,489 and in their yards are sebesarRp. 561 983 so the total income of farmers is Rp. 11,670,472; (2) Contributions vegetables from land use vegetable farmer's yard to income amounted to 5%. Keywords: Land Use Pekarang, Income, Contribution